2007
DOI: 10.1007/s00248-007-9210-9
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Acyl-Homoserine Lactone in Subtidal Biofilm and the Implication in Larval Behavioral Response in the Polychaete Hydroides elegans

Abstract: Quorum sensing (QS) signals have been considered to play important roles in biofilm development and in the attractiveness of biofilms to higher organisms in marine ecosystem. In this study, bacterial QS signalsacylated homoserine lactone derivatives (AHLs) were detected in 2-, 4-, and 6-day-old subtidal biofilms by using AHLs reporter strains. N-dodecanoyl-homoserine lactone (C12-HSL) was identified in 6-day-old biofilm at a concentration of 9.04 microg cm(-minus;2) (3.36 mmol l(-minus;1)). To investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…The observation that only the 1-and 3-day subtidal biofilms could induce coloration of the reporter strain CV026 was similar with that in our previous study, which was carried out at the university pier, a quite different costal marine environment (Huang et al, 2007a). These consistent results suggest that dynamics of AHLs in subtidal biofilms over time may follow similar pattern in coastal marine environments.…”
Section: Dynamics Of Ahls During Subtidal Biofilm Formationsupporting
confidence: 88%
See 1 more Smart Citation
“…The observation that only the 1-and 3-day subtidal biofilms could induce coloration of the reporter strain CV026 was similar with that in our previous study, which was carried out at the university pier, a quite different costal marine environment (Huang et al, 2007a). These consistent results suggest that dynamics of AHLs in subtidal biofilms over time may follow similar pattern in coastal marine environments.…”
Section: Dynamics Of Ahls During Subtidal Biofilm Formationsupporting
confidence: 88%
“…AHL-based QS system was firstly discovered from marine Vibrio fischeri (Milton, 2006). Recently, AHL-producing bacteria were isolated from 'marine snow' (Gram et al, 2002), marine sponges (Taylor et al, 2004;Mohamed et al, 2008), marine water column, eukaryotic algae (Wagner-Dobler et al, 2005) and marine subtidal biofilms (Huang et al, 2007a), suggesting the potential impacts of AHLs in marine bacterial communities. It was proposed that bacteria might use QS as a weapon to compete for survival or to dominate in a natural niche (Waters and Bassler, 2005;Defoirdt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Joint et al 2002). In a previous study, we reported the direct detection of AHLs in marine subtidal biofilms and found that AHLs affected larval behavior in the polychaete Hydroides elegans (Huang et al 2007a). However, the diversity of AHLproducing bacteria in marine biofilms has not been shown.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 94%
“…Therefore, elimination of AHL may thus prevent the development of bacterial fouling [25]. AHL acylase degrades AHL, and as the concentration of this enzyme increases, biofilm formation is inhibited and the settlement of Ulva spores and polychaete larvae is affected [110,111]. Consequently, AHL acylases can also inhibit the settlement of macroorganisms to some extent.…”
Section: Enzymes That Interfere With Intercellular Communicationmentioning
confidence: 99%